2013
DOI: 10.1016/j.neulet.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-late EEG potential evoked by preferential activation of unmyelinated tactile afferents in human hairy skin

Abstract: Human tactile sensibility in hairy skin is mediated not only by fast conducting myelinated (Aβ) afferents, but also by a system of slow conducting, unmyelinated afferents that respond preferentially to light touch, C-tactile (CT) afferents. This system has previously been shown to correlate with the pleasantness of tactile stimuli, where a soft brush moving at 1-3cm/s activates CT afferents strongly. Functional magnetic resonance imaging (fMRI) studies have shown that preferential CT fiber stimulation activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 118 publications
7
42
2
Order By: Relevance
“…It was hypothesized that consistent with the stronger conscious percept and higher amplitude sympathetic skin response previously reported (Olausson et al, , ; Pawling, Trotter, Trotter, McGlone, & Walker, ), a larger amplitude P300 will be measured in response to Aβ‐targeted (30 cm/s) versus CT‐targeted (3 cm/s) touch. Secondly, consistent with the previous report of Ackerley et al (), CT optimal (3 cm/s) stroking is hypothesized to evoke a ULP over frontal electrodes, while 30 cm/s strokes, a stronger stimulus for Aβs, will not. Finally, we explored whether, in line with previous psychophysical and fMRI data (Croy et al, ; Voos et al ), cortical responses to CT‐targeted touch are correlated with self‐reported levels of autistic traits.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…It was hypothesized that consistent with the stronger conscious percept and higher amplitude sympathetic skin response previously reported (Olausson et al, , ; Pawling, Trotter, Trotter, McGlone, & Walker, ), a larger amplitude P300 will be measured in response to Aβ‐targeted (30 cm/s) versus CT‐targeted (3 cm/s) touch. Secondly, consistent with the previous report of Ackerley et al (), CT optimal (3 cm/s) stroking is hypothesized to evoke a ULP over frontal electrodes, while 30 cm/s strokes, a stronger stimulus for Aβs, will not. Finally, we explored whether, in line with previous psychophysical and fMRI data (Croy et al, ; Voos et al ), cortical responses to CT‐targeted touch are correlated with self‐reported levels of autistic traits.…”
Section: Introductionsupporting
confidence: 84%
“…This ultra‐late potential (ULP), first identified as a specific response to laser evoked stimulation of C‐nociceptive fibres is recorded over frontal brain regions (Bragard, Chen, & Plaghki, ; Bromm & Lorenz, ; Bromm, Neitzel, Tecklenburg, & Treede, ; Valeriani et al, ). A ULP evoked by CT‐targeted touch has also been reported (Ackerley, Eriksson, & Wessberg, ) in response to brush strokes delivered to the ventral surface of the forearm at a CT‐optimal velocity (Ackerley et al, ). The ULP peaked around 2700 ms after initial skin contact and continued throughout the brushing stimulus.…”
Section: Introductionmentioning
confidence: 72%
“…In comparison, there is no clinical test for tactile pleasantness; however, this may give a functional insight into the workings of the CT and C-fiber systems. A feasible way of testing the cortical signature of CT fiber function was proposed using controlled stroking with combined electroencephalography (Ackerley et al, 2012b), where an ultra-slow, late cortical potential was seen over more frontal areas.…”
Section: Introductionmentioning
confidence: 99%
“…what, when and where. CT afferents convey gentle touch; however, there is a delay of 41.5 s before the touch information is processed in the brain, due to the slow conduction along the unmyelinated axon (Ackerley et al, 2013). These afferents are hypothesised to signal hedonic information about touch such as pleasantness, which is less useful for precise sensorimotor integration, although likely plays a role in the control and motivation of behaviour, such as driving the need to seek pleasurable, interactive social touch .…”
Section: From the Periphery To The Brainstemmentioning
confidence: 99%